(untitled) (American Journal of Islam and Society, 2022)
This article provides a sketch of the historical antecedent to the 11th century theory of maqāṣid al-sharī‘a (the purposes of the law). I examine the role of human benefit (maṣlaḥa) within the classical Shafi‘i school, focusing on the 10th and 11th centuries. I show that Shafi‘i law gave consideration of benefit a central role in the interpretation of scripture. This is attested to in both texts of legal theory (uṣūl al-fiqh) and substantive law (furū‘ al-fiqh). Importantly, I also explain how Shafi‘is subjected their claims about benefit to contestation and debate, acknowledging the limits to humans’ ability to apprehend God’s law. In presenting this classical model of benefit in the Shafi‘i school, the essay offers an alternative for reformists who invoke the maqāṣid al-sharī‘a today—an alternative that has a deep pedigree within the Islamic tradition and promotes the democratization of debate over the benefits of the law.